Association between sleep-related phenotypes and gut microbiota: a two-sample bidirectional Mendelian randomization study - Wang, Xiaoqiu; Wang, Chi; Liu, Kai; Wan, Qingyun; Wu, Wenzhong; Liu, Chengyong (Frontiers in Microbiology, 2024)
Abstract Background An increasing body of evidence suggests a profound interrelation between the microbiome and sleep-related concerns. Nevertheless, current observational studies can merely establish their correlation, leaving causality unexplored. Study objectives To ascertain whether specific gut microbiota are causally linked to seven sleep-related characteristics and propose potential strategies for insomnia prevention. Methods The study employed an extensive dataset of gut microbiota genetic variations from the MiBioGen alliance, encompassing 18,340 individuals. Taxonomic classification was conducted, identifying 131 genera and 196 bacterial taxa for analysis. Sleep-related phenotypes (SRPs) data were sourced from the IEU OpenGWAS project, covering traits such as insomnia, chronotype, and snoring. Instrumental variables (IVs) were selected based on specific criteria, including locus-wide significance, linkage disequilibrium calculations, and allele frequency thresholds. Statistical methods were employed to explore causal relationships, including Inverse Variance Weighted (IVW), MR-Egger, Weighted Median, and Weighted Mode. Sensitivity analyses, pleiotropy assessments, and Bonferroni corrections ensured result validity. Reverse causality analysis and adherence to STROBE-MR guidelines were conducted to bolster the study's rigor. Results Bidirectional Mendelian randomization(MR) analysis reveals a causative interplay between select gut microbiota and sleep-related phenotypes. Notably, outcomes from the rigorously Bonferroni-corrected examination illuminate profound correlations amid precise compositions of the intestinal microbiome and slumber-associated parameters. Elevated abundance within the taxonomic ranks of class Negativicutes and order Selenomonadales was markedly associated with heightened susceptibility to severe insomnia (OR=1.03, 95% CI: 1.02-1.05, p=0.0001). Conversely, the augmented representation of the phylum Lentisphaerae stands in concord with protracted sleep duration (OR=1.02, 95% CI: 1.01-1.04, p=0.0005). Furthermore, heightened exposure to the genus Senegalimassilia exhibits the potential to ameliorate the manifestation of snoring symptoms (OR=0.98, 95% CI: 0.96-0.99, p=0.0001). Conclusion This study has unveiled the causal relationship between gut microbiota and SRPs, bestowing significant latent value upon future endeavors in both foundational research and clinical therapy.